IMPLEMENTASI METODE HYPNOTEACHING DALAM MODEL PEMBELAJARAN INQUIRY TERHADAP MINAT BELAJAR SISWA PADA MATA PELAJARAN IPS KELAS IV UPT SD INPRES SARITE’NE KABUPATEN GOWA - Siti Nurkhalizah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to describe the implementation of the hypnoteaching method in the inquiry learning model and its impact on students' learning interest in the social studies subject of class IV UPT SD Inpres Sarite'ne, Gowa Regency. This study uses a qualitative descriptive research method. With a focus on observing the process of student role play and their self-motivation, the sampling technique used in this study was the control class (experimental and quasi-experimental). The sample used in this study was all 39 students in class IV. Data collection techniques used in this study were observation, data collection in the field, interviews and documentation. The data analysis used was by reducing data, presenting data, and drawing conclusions. The results of the study indicate that the hypnoteaching method has the potential to increase students' interest in learning social studies in class IV of UPT SD Inpres Sarite'ne, Gowa Regency, showing that class IV A out of 20 students who achieved the KKM score were 8 people or 40% and those who did not achieve the KKM score were 12 people or 60% with an average score of 70 and in class IV B out of 19 students who achieved the KKM score were 9 people or 47% and those who did not achieve the KKM score were 10 people or 53%. Based on the results of the study above, it can be concluded that the interest in learning social studies of class IV students of UPT SD Inpres Sarite'ne, Gowa Regency through the application of the hypnoteaching method in the inquiry learning model has increased.